PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI BALAI KONSERVASI TUMBUHAN KEBUN RAYA EKA KARYA BALI - Ni Nyoman Lidyantari; I Wayan Arta Artana; IGAB Widiantara (Journal of Tourism and Interdiciplinary Studies, 2021)
An organization manage HR with disciplined attitudes and behavior. Employee discipline can have a strong impact on an organization to achieve success. This study aims to determine the effect of compensation and work discipline partially on employee performance at the "Eka Karya" Botanical Garden Plant Conservation Center in Bali, which in one year in 2018 showed that there were employee delays above 47.10%. Therefore, the authors conducted a study by testing the hypothesis about how much influence compensation and work discipline had on employee performance at the Bali Botanic Garden. The approach of this research is quantitative research. So, to answer this hypothesis, it is done by taking a sample of 99 respondents. Data were tested using validity, reliability and classical assumptions and analyzed by multiple linear regression, T test, and F test. Based on the results of the analysis, a conclusion can be drawn as follows: Compensation (X1) has a positive and significant effect on performance (Y) at the Botanical Gardens Conservation Center "Eka Karya" Bali. The amount of regression coefficient b1X1 which is positive is 0.356. This test is supported by a statistical test t (t - test) which states that t count is greater than t table, which means H1 is accepted. Work discipline (X2) has a positive and significant effect on performance (Y) in the Botanical Gardens Conservation Center "Eka Karya" Bali. This can be seen from the regression coefficient b2X2 which is positive at 0.218. This test is supported by a statistical test t (t-test) which states that t count is greater than t table, which means H2 is accepted. Simultaneously compensation (X1) and work discipline (X2) have a positive and significant effect on performance (Y) in the Botanical Gardens Conservation Center "Eka Karya" Bali. This is evidenced through multiple regression analysis Y = 20,556 + 0,356X1 + 0,218X2. In addition, it is confirmed by the F (F-test) test where F count is greater than F table, which means Ho is rejected and H3 is accepted. Compensation is the dominant variable that influences performance in the Botanical Gardens Conservation Center "Eka Karya" Bali with a standarized beta coefficient of 0.553.